(untitled) (LACCEI, 2024)
The present systematic review aimed to describe the bibliometric and engineering aspects regarding the role of business intelligence as a competitive advantage in organizations between 2012 and 2022. In this sense, a search was initiated in various scientific databases such as: Scopus, Scielo, Dialnet, Redalyc, Alicia, Dspace, Crossref and Openaire using the following keywords: business intelligence, data management, ETL, decision making, Peru, data mining, organizational approach, datamart, competitive intelligence and artificial intelligence. Subsequently, inclusion and exclusion criteria were applied corresponding to the presence of the study variable in the title, language, year of publication, publication in open Access, type of research, quantitative results of the study, among other criteria. The bibliometric results showed that during the years 2021-2022 applied research in business intelligence has increased, 59% of identified studies have been published in Spanish and 41% in English, while Scopus, Scielo and Dialnet are the databases with the largest amount of research in this regard. In the case of the content results, tools associated with business intelligence and the most relevant effects achieved with their implementation were identified. Finally, it was concluded that business intelligence represents a competitive advantage for organizations due to its positive impact on decision making, resource optimization and efficiency levels.